Impaired expression of neuronal nitric oxide synthase in the gracile nucleus is involved in neuropathic changes in Zucker Diabetic Fatty rats with and without 2, 5-hexanedione intoxication. (May 2016) - Ma, Sheng-Xing; Peterson, Richard G.; Magee, Edward M.; Lee, Paul; Lee, Wai-Nang Paul; Li, Xi-Yan
Highlights: We report selective impairment of nNOS expression in the gracile nucleus in ZDF rats. nNOS expression is up-regulated in the gracile nucleus by 2, 5-HD intoxication in rats. 2, 5-HD-induced nNOS expression in the gracile nucleus is attenuated in ZDF rats. We examine functional neuropathic changes in the rats with and without intoxication. Impaired gracile nNOS levels is involved in neuropathic pathophysiology in ZDF rats. Abstract: These studies examined the influence of 2, 5-hexanedione (2, 5-HD) intoxication on expression of neuronal nitric oxide synthase (nNOS) in the brainstem nuclei in Zucker Diabetic Fatty (ZDF) vs. lean control (LC) rats. Functional neuropathic changes were also investigated following axonal damage and impaired axonal transport induced by the treatment. Animals were intoxicated by i.p. injection of 2, 5-HD plus unilateral administration of 2, 5-HD over the sciatic nerve. The mechanical thresholds and withdrawal latencies to heat and cold stimuli on the foot were measured at baseline and after intoxication. The medulla sections were examined by nNOS immunohistochemistry and NADPH-diaphorase histochemistry at the end of the treatments. The mechanical thresholds and withdrawal latencies were significantly decreased while nNOS immunostained neurons and NADPH-diaphorase positive cells were selectively reduced in the gracile nucleus at baseline in ZDF vs. LC rats. NADPH-diaphorase reactivity and nNOS positive neurons were increased in the ipsilateral gracile nucleus in LC rats following 2, 5-HD intoxication, but its up-regulation was attenuated in ZDF rats. These results suggest that diabetic and chemical intoxication-induced nNOS expression is selectively reduced in the gracile nucleus in ZDF rats. Impaired axonal damage-induced nNOS expression in the gracile nucleus is involved in neuropathic pathophysiology in type II diabetic rats.